2018
DOI: 10.1111/ecc.12807
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Dutch extended Cancer Survivors’ Unmet Needs measure (CaSUN-NL)

Abstract: Information and support needs increase emotional distress and can impede cancer survivors’ adjustment. To investigate the information and support needs of Dutch cancer survivors, the Cancer Survivors’ Unmet Needs measure (CaSUN) was translated into Dutch and applied in two Dutch studies with cancer survivors (N = 255; N = 467). The CaSUN‐NL entailed the original five CaSUN scales, extended with respectively a returning to work and lifestyle scale. This study aimed to determine the psychometric properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 40 publications
8
25
0
Order By: Relevance
“…[54] Of those, 4 studies recruited breast cancer patients, [4648,51] and 4 other studies recruited subjects with head and neck cancer, prostate cancer, hematological cancer, and lung cancer, respectively. [49,50,52,53] Moreover, 8 studies were carried out in inpatient setting, [29,30,35,4446,52,53] 17 in outpatient setting, [1416,23,25,28,3236,39,40,47,48,51,52] 8 in inpatient and outpatient settings, [22,24,27,38,41,42,45,46] and 4 studies did not report where the study was conducted. [13,29,31,54] (Table 1)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[54] Of those, 4 studies recruited breast cancer patients, [4648,51] and 4 other studies recruited subjects with head and neck cancer, prostate cancer, hematological cancer, and lung cancer, respectively. [49,50,52,53] Moreover, 8 studies were carried out in inpatient setting, [29,30,35,4446,52,53] 17 in outpatient setting, [1416,23,25,28,3236,39,40,47,48,51,52] 8 in inpatient and outpatient settings, [22,24,27,38,41,42,45,46] and 4 studies did not report where the study was conducted. [13,29,31,54] (Table 1)…”
Section: Resultsmentioning
confidence: 99%
“…The reliability, responsiveness and validity assessment of the included instruments were presented in S3 and S4 Tables, respectively. Regarding the quality of measurement properties, internal consistency was evaluated in 32 studies with 9 studies showing negative rating [16,23,31,32,34,40,43,51,53] and 4 studies indeterminate rating. [28,29,36,42] Less than half of the studies assessed test-retest reliability (13/37, 35.1%), and only 4 studies showed positive scoring.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are mostly qualitative studies (10)(11)(12) or small-scale cross-sectional studies (13) focusing on the psychosocial problems. The studies indicated that the Indonesian gynecological cancer survivors experienced a high level of fear of cancer recurrence (13), altered selfconcept (11), altered sexual function and intimate relationships (10,11), as well as physical discomfort (11). A phenomenology study conducted in province in Indonesia found that one of the cervical cancer survivors' needs to survive from cancer was the support from the family and the health care providers.…”
Section: Introductionmentioning
confidence: 99%